Robin Hood of Sherwood Forest. - McGovern, Ann.; Spilka, Arnold (New York, Scholastic., 1968)
Ten adventures of the legendary outlaw who, with his band, vowed to bring woe to both the greed rich and those without mercy, and to help the innocent and good-hearted.
Faculty.
Keywords: Robin Hood (Legendary character) -- Legends; Robin Hood (Legendary character) -- Legends